Handling electronic information for mechanical systems design. (19th April 2004) - Allen, R.D.; Hicks, B.J.; Culley, S.J.
The success of a product and ultimately the company is very dependent on the ability of the company to produce an optimal design efficiently. In order to achieve this, the organisation must drive down time to market and possess the ability to make fully informed decisions at the early phase of the design process. These decisions can include component selection, reliability, suppliers, as well as cost and maintenance considerations. Today, computer modelling and "electronic catalogues" are becoming the preferred choice for rapidly carrying out the evaluation of design alternatives. In using such techniques, the designer demands the capability to select and evaluate mechanical components both quantitatively and qualitatively. The former pertains to the components contribution to the overall performance capability of the system whilst the latter relates to the utilisation of the components, with respect to best or recommended practices, cost, preferred supplier, component standardisation and reliability issues. This paper describes the use of electronic information in the design of mechanical systems and the limitations of current technology. The need to integrate electronic information systems to better enable a company's ability to produce an optimal product is discussed and the requirements for this are described. To address the issue of information integration for the identification and selection of mechanical components a methodology for the development of XML schemas that represent data describing mechanical components is developed, with a number of example applications.